Determinants of Online Training in Increasing Productivity for Sustainable SMEs in Southwest Papua Province - Winarsih, Winarsih (Maneggio, 2025)
This study aims to identify and analyze the determinants influencing the effectiveness of online training in increasing productivity and supporting the sustainability of small and medium enterprises (SMEs) in Southwest Papua Province. The research method used is descriptive qualitative with a field study approach. Data were obtained through in-depth interviews, observation, and documentation with SMEs participating in online training, instructors, and local government officials. Informants were selected using purposive sampling, focusing on SMEs actively involved in online training programs. The results indicate that the success of online training is influenced by five main factors: access to technology and digital infrastructure, the quality and relevance of training materials, instructor competence, participant motivation, and support from the government and related institutions. Online training has been proven to increase SME productivity, particularly in production efficiency, digital marketing, and increased turnover. However, the impact is not evenly distributed due to limited infrastructure and digital literacy. Contributions to SME sustainability are more visible in the economic and social aspects, while environmental aspects remain less well-regarded. This study confirms that online training has significant potential to drive the digital transformation of SMEs in Southwest Papua, provided there are improvements in technological support, mentoring, and the integration of sustainable business concepts.